Terje Aven Availability Model Application to the N-1 System with One Unit of Backup Towing Motor Components for Kiln Machine Preventive Maintenance - Adianto, Hari; Nashar, Gifari Bayu; Susanto, Sani; Syah Tjaja, Arief Irfan (Jurnal Improsci, 2024)
The kiln machine is one of the pieces of machinery used to produce granite tiles. One of its many crucial components is the towing motor. The production process requires a high-performance and easily accessible kiln unit because it lasts for 24 hours. As a result, there will be less downtime since the extra towing motor can take the place of the damaged one. The Terje Aven availability model calculates the number of towing motor reserves. The availability of kiln equipment has not yet achieved its full potential because the company currently has six backup towing motors.